AGEs induce high expression of Dll4 via endoplasmic reticulum stress PERK signaling-mediated internal ribosomal entry site mechanism in macrophages - Yanpeng Ma; Shixiang Zheng; Xiqiang Wang; Ling Zhu; Junkui Wang; Shuo Pan; Yong Zhang; Zhongwei Liu (Heliyon, 2023)
Background and aim: Advanced glycation end products (AGEs)- exposed macrophages was characterized by Delta-like ligand 4 (Dll4) high expressed and has been shown to participate in diabetes-related atherosclerosis. This study was aimed to investigate the translational regulatory mechanism of Dll4 high expression in macrophages exposed to AGEs. Methods: Human Dll4 5′ untranslated region (5′UTR) sequence was cloned and inserted into a bicistronic reporter plasmid. Human THP-1 macrophages transfected with the bicistronic reporter plasmids were exposed to AGEs. Dual-luciferase assay was used to detect internal ribosome entry site (IRES) activity contained in Dll4 5′UTR. Small interference RNA transfection was used to knock-down specific gene expression. Localization of protein was analyzed. Results: AGEs exposure significantly induced IRES activity in Dll4 5′ UTR in human macrophages. Internal potential promoter and ribosome read-through mechanisms were excluded. Inhibition of endoplasmic reticulum stress and specific silencing of protein kinase R-like endoplasmic reticulum kinase (PERK)/eukaryotic initiation factor 2α (eIF2α) signaling pathway activation reduced IRES activity in Dll4 5′ UTR in human macrophages. Dll4 5′ UTR IRES activity was also inhibited by targeted silencing of heterogeneous nuclear ribonucleoprotein A1 (hnRNPA1). Moreover, specific inhibition of PERK/eIF2α signaling pathway led to deactivation of hnRNPA1, resulting to reduction of AGEs- induced Dll4 5’ UTR IRES activity in human macrophages. Conclusions: AGEs induced Dll4 5′ UTR IRES activity in human macrophages which was dependent on endoplasmic reticulum stress PERK/eIF2α signaling pathway. hnRNPA1 acted the role as an ITAF was also indispensable for AGEs-induced Dll4 5′UTR IRES activity in human macrophages.